An Insight into the Characteristic Equation for an Integer Program - Santosh Kumar (International Journal of Mathematical, Engineering and Management Sciences, 2021)
This article enhances properties and applications associated with the characteristic equation (CE) developed to find an optimal and other ranked-optimal solutions of linear integer programming model. These enhanced properties have applications in the analysis of the multi-objective linear integer programs. The paper also identifies why the CE approach is not possible for some special linear programming (LP) models and creates a challenge for further investigation.